WACANA KESETARAAN GENDER DALAM MEDIA ONLINE: STUDI ANALISIS WACANA KRITIS TERHADAP PEMBERITAAN PEREMPUAN - Malikha, Usrin (Jurnal Tinta, 2023)
This study aims to reveal how gender equality is represented in online media through the Critical Discourse Analysis (CDA) approach based on Fairclough’s model. The main focus of this research is to analyze how media discourse construction can either reinforce or deconstruct gender stereotypes toward women. The research data consist of online news texts taken from major Indonesian news portals between 2023 and 2024, specifically news related to women in political, economic, and social contexts. This study employs a descriptive qualitative method using three dimensions of analysis: textual, discursive practice, and social practice. The findings reveal that the media tend to portray women ambivalently on one hand, as empowered agents in public spheres, yet on the other, still frequently depicted as victims or passive objects, particularly in news related to violence. These findings indicate that media representation is not entirely neutral on gender issues. Therefore, critical awareness in media language use is essential to promote gender equality more fairly and proportionally.